Becoming the perfect partner: How to develop a car sharing service that satisfies the needs of the users, the stakeholders and possible future partners - Snedsböl, Hanne (My University, 2020)
Today’s society is too dependent on transportations by privately owned cars that it is no longer sustainable. One step to steer the development toward a sustainable future is to offer environmentally friendly alternatives as a replacement to the private owned car. GreenMotion is a rental company that strives to offer carsharing with the lowest possible climate impact. In 2018, they started their work to develop a rental concept where rental cars could be provided counterless through self-service in the Drive & Go application to the customer. This reduced the number of employees, company buildings and the time it takes the customer to rent a car. The concept was developed in-house by GreenMotion and was therefore in the need of an external analysis during the launch in Sweden 2020. Becoming the Perfect Partner is about exploring the carsharing market’s end-users, stakeholders and possible future partners in Sweden, getting to know their needs and requirements and with this as a basis find a balance between them and create the best possible carsharing service. This was done with a service design approach by using methods like actor map, netnography, literature review and interviews. Early in the project, interest arose regarding Mobility as a Service and the opportunities that a collaboration with such an actor could bring. Therefore, the project was directed to investigate how GreenMotion could become the perfect partner to MaaS. The project resulted in add-ons to the Drive & Go application, an improved customer journey of the service, suggested future partners, and insights into what factors that is required to participate in MaaS. The results found are largely in line with previous research on MaaS and was confirmed in the study. The thesis has also added knowledge about the difficulty for companies to maintain their corporate identity as a transport supplier to MaaS, and that a close interaction between the services is required to achieve a successful collaboration. In addition, the users have a need for a well-functioning “full service”, where everything from the usability of the application to how well the customer service works.
Keywords: MaaS, Carsharing, Collaboration, Iteration, Usability, Requirements